2007
DOI: 10.1007/s10295-007-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Mixture design as a first step for optimization of fermentation medium for cutinase production from Colletotrichum lindemuthianum

Abstract: Cutinase enzymes from fungi have found diverse applications in industry. However, most of the available literature on cutinase production is related to the cultivation of genetically engineered bacteria or yeast cells. In the present study, we use mixture design experiments to evaluate the influence of six nutrient elements on production of cutinase from the fungus Colletotrichum lindemuthianum. The nutritional elements were starch, glucose, ammonium sulfate, yeast extract, magnesium sulfate, and potassium pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
2
27
1
1
Order By: Relevance
“…In 2007, Rispoli and Shah [18] studied the production of cutinase from Collerotrichum lindemuthianum, and found that yeast extract had a strong positive influence on the yield of the process.…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, Rispoli and Shah [18] studied the production of cutinase from Collerotrichum lindemuthianum, and found that yeast extract had a strong positive influence on the yield of the process.…”
Section: Resultsmentioning
confidence: 99%
“…Sathish et al [8] and Yan et al [14] also noticed that quadratic model is best suitable model for analysis of the mixture design. The special cubic and cubic models have the higher R [11] the model which have the higher R value and lower P value are significant based on this the cubic and special cubic models were rejected and further analysis was carried out with the quadratic model only.…”
Section: Mixture Designmentioning
confidence: 99%
“…Mixture experiment design has been used as an alternative to factorial experiments in elucidating the effects of nutrient proportions in plant-herbivore relationships [10]. Mixture experiments have become a subject of many studies and have also been extensively applied in biotechnology, pharmaceuticals, geology, petroleum, food, and tobacco industries [8,11]. In the present study, mixture design was employed to evaluate the influence of mixed solid substrates on the FTase production by isolated Aspergillus awamori GHRTS.…”
Section: Introductionmentioning
confidence: 99%
“…The production of secondary metabolites in the bacterial cells are largely known to depend upon the constituents of the medium in which they are grown [47][48][49]; however, little is known about the effect of media formulations on protein folding and accumulation of soluble fractions [50].…”
Section: Culture Media Optimizationmentioning
confidence: 99%